ARAHAN PENATAAN RUANG TERBUKA HIJAU PADA KORIDOR JALAN JENDRAL SUDIRMAN KOTA SINGKAWANG - Sasmita, Dwi Fitri (Jurnal Tataloka, 2009)
As one of the primary artery roads and also link connecting various important activities in Singkawang, SudirmanStreet has an important role as the main entrance as well as image of Singkawang. Lack of trees and also lower appraisal towardaesthetical value result in many environmental problems such as dirt, heat and noisy which the community in Sudirman Street corridorhave to deal with. This research aims to result on instruction settlement of Green Open Space at Sudirman Street corridor to beable to improve its environmental quality, especially in Sudirman Street corridor, and Singkawang in general. This research is conductedby using descriptive qualitative, normative, and assumptive analysis method. Based on the analysis result, it is figured outthat the proper concept for Green Open Space in Sudirman Street corridor shall be instructions of concept and strategy which areadjusted with both physical and non-physical condition of Sudirman Street corridor. For this reason, active participation and coordinationbetween the government and community is highly needed.